A Pure Nongestational Choriocarcinoma of Ovary: Sharing Experience in Sabah - Mohd Faizal A.; Dianie DJK.; Suguna S.; Soon R.; Moharzudi M. (Department of Surgery, UKM Medical Centre, 2015)
A pure ovarian choriocarcinoma is a very rare disease which can be either pregnancy related (gestational), may not be related (non-gestational), or commonly correlated with different type of germ cell; teratocarcinoma, dysgerminoma or undifferentiated carcinoma. A pure non-gestational primary ovarian choriocarcinoma is astronomically uncommon and we recorded such condition in 14-year-old teenage girl’s ovary. An abdominal operative procedure with the help of a careful histopathology examination revealed choriocarcinoma in absence of other type of germ cell element. Multiple courses of Etoposide/Methotrexate/Actinomycin-D (EMA) regime of chemotherapy were shown to be effective in this case.